2023
DOI: 10.3390/cancers15205008
|View full text |Cite
|
Sign up to set email alerts
|

EAU Biochemical Recurrence Risk Classification and PSA Kinetics Have No Value for Patient Selection in PSMA-Radioguided Surgery (PSMA-RGS) for Oligorecurrent Prostate Cancer

Fabian Falkenbach,
Francesca Ambrosini,
Pierre Tennstedt
et al.

Abstract: Objective: To assess the influence of biochemical recurrence (BCR) risk groups and PSA kinetics on the outcomes of radioguided surgery against prostate-specific membrane antigen (PSMA-RGS). Currently, neither BCR risk group nor PSA doubling time (PSA-DT), or PSA velocity (PSA-V) are actively assigned or relevant for counseling prior to PSMA-RGS. Methods: We retrospectively analyzed PSMA-RGS cases for oligorecurrent prostate cancer between 2014 and 2023. BCR risk groups, PSA-DT, and PSA-V were analyzed as predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Falkenbach et al . classified 222 patients into the EAU BCR risk group to assess their influence on the outcomes of radioguided surgery against prostate-specific membrane antigen 15 , among which 57.7% of patients had previously undergone salvage radiotherapy. Authors concluded that neither EAU criteria nor the kinetic parameters of PSA were correlated with BCR-free and therapy-free survivals.…”
Section: Discussionmentioning
confidence: 99%
“…Falkenbach et al . classified 222 patients into the EAU BCR risk group to assess their influence on the outcomes of radioguided surgery against prostate-specific membrane antigen 15 , among which 57.7% of patients had previously undergone salvage radiotherapy. Authors concluded that neither EAU criteria nor the kinetic parameters of PSA were correlated with BCR-free and therapy-free survivals.…”
Section: Discussionmentioning
confidence: 99%
“…However, the greatest challenge lies in selecting the ideal candidate, as reliable biomarkers, nomograms or imaging techniques are not yet conclusive [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we attempted to evaluate the role of the European Association of Urology (EAU) risk groups for BCR and PSA kinetics (including PSA doubling time and PSA velocity) in the selection of patients for PSMA-RGS. According to their results, neither BCR risk groups nor PSA kinetics have an impact on the prediction of complete biochemical response, BCR-free and treatment-free survival in PSMA-RGS performed at low PSA values [ 8 ].…”
Section: Introductionmentioning
confidence: 99%